University Friendship: Its Need and Quality during Distance Education - Mahahasneh , Randa Ali; Shehade , Sara Emad (Dirasat: Human and Social Sciences, 2024)
Objectives: The study aimed to identify the nature of university friendship during the transition of education systems to distance education, and how distance education affected the way students formed their friendships, as well as revealing the level of the need to form friendships, the level of its quality, and the relationship between them. Methods: The study followed a mixed descriptive approach (quantitative and qualitative). The study sample consisted of (555) male and female students from the second and third years who began their university studies remotely. Two scales were developed to collect quantitative data, including the need for the friendship scale, and the quality of friendship scale. Personal interviews were conducted with ten students to collect the qualitative data. Results: The results showed that the level of need for friendship among university students during distance education was moderate in general and high for the need for psychological and academic support, and the level of friendship quality was high. In addition, a statistically significant direct correlation was found between the need for friendship and its quality. Conclusions: The quantitative and qualitative results confirmed that there is a great need to form university friendships to provide psychological and academic support. It also turns out that electronic friendships, despite their quality, are not as good as traditional friendships in terms of depth, durability, and continuity. The study recommended conducting further studies on electronic university friendships considering other variables such as academic achievement, age, and students’ social and economic status.